Ayurvedic Management of Tamaka Swasa w.s.r to Bronchial Asthma (International Journal of Ayurveda and Pharma Research, 2022)
Bronchial asthma is one of the most distressing chronic illness in all socio- economic status people, affecting all age groups. Changing in lifestyle, demographic factors, urbanization, environmental charges are the triggering factors of bronchial asthma. Tamaka swasa is characterized by paraoxysmal attacks of breathlessness, cough, coryza, due to chest tightness, rapid respiration, distress inability to expectorate and prolonged expiration. Methods: This is a single case study of a 34 year male patient, came with the complaints of difficulty in Breathing since 5 years. He also complaints of abdominal distension and decreased appetite. According to patient, he was apparently well before 5 years. Gradually he developed breathing difficulty because of his smoking habit. Patient also c/o abdominal distension and decreased appetite at that time. In the case study patient was given Sadhyo vaman first followed by Snehapana with Brahmi ghrta was given along with Internal medications. Result: Patient showed remarkable improvement in severity of symptoms and as well as time period between 2 successive episodes of dyspnea is increased. During this course we observed that the patient had partial relief of symptoms. Lesser the chronicity greater the relief and improvement in chronic condition was observed. Interpretations and Conclusion: The patient was given Sadhyovamana, followed by Snehapana with Brahmi ghrtam for Virechana. The contents of Brahmi ghrtham are Ghee, Brahmi, Shankapushpi, Trikatu, Shweta trivrt, Krishna Trivrt, Vidanga, Nipadruma, Saptala, Danti, followed by Virechana with Trivrt lehaya. Tamake tu virechana In this condition Virechana is advised as the best line of treatment, and in the above mentioned case after Virechana patient feels better and got much more relief from symptoms.